A job for Jenny Archer - Conford, Ellen (Boston : Little, Brown, 2004)
Convinced that her family is poor because her parents refuse to get her a horse or a swimming pool, nine-year-old Jenny Archer follows her own path to making money, including a plunge into real estate that puts her house on the market.
G2
Keywords: Wealth -- Fiction; Moneymaking projects -- Fiction; Humorous stories